2019
DOI: 10.1021/acs.inorgchem.9b01472
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Hybrid Heterometallic Halides with Low-Dimensional Structures and Red Photoluminescence Emissions

Abstract: In recent years, although low-dimensional hybrid lead halides have received great attention due to the fascinating photoluminescent (PL) properties, the research is still on the early stage and only limited phases have been explored and characterized. Here, by introducing heterometals as mixed structural compositions and optical activity centers, we prepared a series of low-dimensional hybrid heterometallic halides, namely as, [(Me)-DABCO]2Cu2PbI6, [(Me)2-DABCO]2M5Pb2I13 (M = Cu and Ag) and [(Me)2-DABCO]­Ag2Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…where I PL is the emission intensity at different temperature (T), I 0 is the emission intensity at 80 K, E a belongs to the activation energy related to the thermally activated non‐radiation process, and k B represents the Boltzmann constant (Figure a and 6b). The theoretical fittings give the activation energies E a of 72±7.062 meV and 56±6.181 meV for compounds 1 and 2 , respectively, which are close to those of hybrid metal halides (R) 2 CdBr 4 ⋅ DMSO (R=C 6 (CH 3 ) 5 CH 2 N(CH 3 ) 3 , 48 meV), (C 4 H 14 N 2 ) 2 In 2 Br 10 (61.8 meV), [(Me)‐DABCO] 2 Cu 2 PbI 6 (73 meV), etc …”
Section: Resultssupporting
confidence: 54%
“…where I PL is the emission intensity at different temperature (T), I 0 is the emission intensity at 80 K, E a belongs to the activation energy related to the thermally activated non‐radiation process, and k B represents the Boltzmann constant (Figure a and 6b). The theoretical fittings give the activation energies E a of 72±7.062 meV and 56±6.181 meV for compounds 1 and 2 , respectively, which are close to those of hybrid metal halides (R) 2 CdBr 4 ⋅ DMSO (R=C 6 (CH 3 ) 5 CH 2 N(CH 3 ) 3 , 48 meV), (C 4 H 14 N 2 ) 2 In 2 Br 10 (61.8 meV), [(Me)‐DABCO] 2 Cu 2 PbI 6 (73 meV), etc …”
Section: Resultssupporting
confidence: 54%
“…Due to the advantages of earth abundance, low toxicity, and low cost, copper (Cu)-based functional material has become a suitable choice to form Cu­(I)-based metal halides. , Recently, Hosono and co-workers first reported Cs 3 Cu 2 I 5 with efficient blue emission, which triggered the exploration of Cu­(I)-based metal halide luminescence materials . However, despite highly efficient blue/green emission, the suboptimal excitation peak position (∼300 nm) of the reported all-inorganic Cu + -based metal halides greatly restricted their further commercial applications. Besides, organic–inorganic hybrid metal halides are an interesting family of functional materials with impressive structural diversity and enormous application prospects. ,, Unlike inorganic solids, the organic–inorganic hybrid metal halides allow us to artificially design the connectivity of an inorganic lattice by choosing suitable organic components. For example, Li et al reported a lead-free Cu­(I)-based organic–inorganic perovskite-related material [K­(C 8 H 16 O 4 ) 2 ] 2 [Cu 4 I 6 ] with one-dimensional (1D) clusters, which exhibits greenish-yellow emission (545 nm) with a near-unity PLQY (∼97.8%) . However, the photoluminescence excitation (PLE) spectrum shows that blue light is still not located in the optimal excitation region.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide-based complexes with diverse organic species usually exhibit distinct photophysical properties and have extensive applications in optical devices, sensors, and white-light-emitting materials. Thus, the luminescent emission band for 1 was performed. Upon UV-light irradiation (λ ex = 300 nm), the solid displayed a broad and weak emission band with a peak of 660 nm at ambient temperature.…”
mentioning
confidence: 99%